Pre-contractual justice in a comparative perspective: Striking the right balance - Frauenknecht, Sigrid Anne (Department of Private Law, 2023)
One of the most important reasons for doing comparative work in the field of law is to get a better understanding of the legal jurisdictions of other countries. Studying the law of another country also enables one to understand one's own legal jurisdiction better. It helps one to see well-established principles in a new light and to ask questions about the continued applicability of such principles.